A Dipolar Anthracene Dye: Synthesis, Optical Properties and Two‐photon Tissue Imaging. Issue 18 (8th September 2016) - Moon, Hyunsoo; Jun, Yong Woong; Kim, Dokyoung; Ryu, Hye Gun; Wang, Taejun; Kim, Ki Hean; Huh, Youngbuhm; Jung, Junyang; Ahn, Kyo Han
Abstract: Two‐photon microscopy is a powerful tool for studying biological systems. In search of novel two‐photon absorbing dyes for bioimaging, we synthesized a new anthracene‐based dipolar dye (anthradan) and evaluated its two‐photon absorbing and imaging properties. The new anthradan, 9, 10‐bis( o ‐dimethoxy‐phenyl)‐anthradan, absorbs and emits at longer wavelengths than acedan, a well‐known two‐photon absorbing dye. It is also stable under two‐photon excitation conditions and biocompatible, and thus used for two‐photon imaging of mouse organ tissues to show bright, near‐red fluorescence along with negligible autofluorescence. Such an anthradan thus holds promise as a new class of two‐photon absorbing dyes for the development of fluorescent probes and tags for biological systems. Abstract : Born two dye : A new anthracene‐based dipolar dye (anthradan) was synthesized and evaluated its two‐photon absorbing and imaging properties. 9, 10‐Bis( o ‐dimethoxy‐phenyl)‐anthradan absorbs and emits at longer wavelengths than acedan, a well‐known two‐photon absorbing dye, and was used for two‐photon imaging of mouse organ tissues with negligible autofluorescence.